Letter - Prestwich, J. W.
037-0170-001 TELEGRAPHIC ADDRESS: "WHOLESALE, MANCHESTER" TELEPHONE: BLACKFRIARS 1212. PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, SECRETARY'S OFFICES, 1, BALLOON STREET, MANCHESTER, 4 OUR REFERENCE: JWP/RA/WN. YOUR REFERENCE: 27th May, 1937. Dear Mr.Tewson, Further to your telephonic conversation with Mr. Lancaster on Monday last, regarding the arrival in England of the 4,000 Basque refugee children, I am pleased to advise you that my Directors have agreed to supply goods to the value of £250 and I note from our telephonic conversation this morning that you are consulting your Joint Committee as to the nature of the goods you desire to be supplied. In the meantime, as you desire, I am arranging for delivery of biscuits to the value of £10 immediately and I have asked Mr. A.E. Newman, our Branch Administrative Officer, of 99, Leman Street, London. E.1, to arrange accordingly in conjunction with your goodself. Mr. Newman will be at your service in regard to the further delivery of goods to the value stated, the nature of which you will ultimately decide upon. J.W. Prestwich, Deputy Secretary and Executive Officer. Mr. Tewson, Assistant Secretary, Trade Union Congress, Transport House, Smith Square, WESTMINSTER, London. S.W.1. 292/946/37/170